2024
DOI: 10.1021/acsabm.3c01194
|View full text |Cite
|
Sign up to set email alerts
|

Low-Concentration Gelatin Methacryloyl Hydrogel with Tunable 3D Extrusion Printability and Cytocompatibility: Exploring Quantitative Process Science and Biophysical Properties

Soumitra Das,
Remya Valoor,
Praneeth Ratnayake
et al.

Abstract: Three-dimensional (3D) bioprinting of hydrogels with a wide spectrum of compositions has been widely investigated. Despite such efforts, a comprehensive understanding of the correlation among the process science, buildability, and biophysical properties of the hydrogels for a targeted clinical application has not been developed in the scientific community. In particular, the quantitative analysis across the entire developmental path for 3D extrusion bioprinting of such scaffolds is not widely reported. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This is because the 45S5 BG used is of micron-scale being susceptible to precipitation during the preparation process, which leads to a decrease in the mechanical properties due to possible particle agglomeration. Also, Das and Basu utilized nanoscale HA as an inorganic filler to obtain a mechanically superior composite hydrogel. , Song et al also reported the use of HA as an inorganic filler to obtain a porous composite hydrogel of GelMA/HA, but with better mechanical properties than GelMA. Zheng et al provided more insight into the decrease in compressive modulus of hydrogels with the addition of 45S5 BG particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the 45S5 BG used is of micron-scale being susceptible to precipitation during the preparation process, which leads to a decrease in the mechanical properties due to possible particle agglomeration. Also, Das and Basu utilized nanoscale HA as an inorganic filler to obtain a mechanically superior composite hydrogel. , Song et al also reported the use of HA as an inorganic filler to obtain a porous composite hydrogel of GelMA/HA, but with better mechanical properties than GelMA. Zheng et al provided more insight into the decrease in compressive modulus of hydrogels with the addition of 45S5 BG particles.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis process of GelMA was based on a method reported in the literature . Briefly, 10 w/v % GEL was dissolved in 100 mL of DPBS at 60 °C under continuous stirring until fully dissolved.…”
Section: Methodsmentioning
confidence: 99%